Research of influence of credit portfolio quality on efficiency of credit activity of bank as constituent of credit risk monitoring - Рац, Ольга Миколаївна (Technology audit and production reserves, 2015)
The analysis of trends in bank lending showed the need to improve credit risk management. In the article it is revealed that central position in the credit risk management covers assessment and monitoring of risks as part of credit policy of banks. The process of credit monitoring of bank is constructed by author, peculiarities of monitoring of credit risk of bank at different levels are revealed. The interrelation between indicators of quality of the credit portfolio and the efficiency of banking operations is investigated. It is investigated regression multifactor model of dependence of particular quality indicators of the credit portfolio and profitability of lending operations. It is revealed that the greatest influence on a productive indicator is the ratio of bank’s own funds and the credit portfolio, the loss ratio of the credit portfolio, the ratio of protection from credit losses. The use of this model in functioning practice of banking institutions will allow to establish the degree of influence of individual parameters on the efficiency of the credit portfolio of credit operations of the bank, to diagnose a "border" riskiness of the bank, to predict changes in the quality of the credit portfolio.